Epidermal multinucleated giant cells are not always a histopathologic clue to a herpes virus infection: multinucleated epithelial giant cells in the epidermis of lesional skin biopsies from patients with acantholytic dermatoses can histologically mimic a - Philip R. Cohen; Taraneh Paravar; Robert A. Lee (Mattioli1885, 2014)
Background: Multinucleated giant cells in the epidermis can either be epithelial or histiocytic. Epithelial multinucleated giant cells are most often associated with herpes virus infections. Purpose: To review the histologic differential diagnosis of conditions with epithelial and histiocytic multinucleated giant cells-since multinucleated giant cells in the epidermis are not always pathognomonic of a cutaneous herpes virus infection-and to summarize dermatoses in which herpes virus infection has been observed to coexist. Methods: Two individuals with acantholytic dermatoses whose initial lesional skin biopsies showed multinucleated epithelial giant cells suggestive of a herpes virus infection are reported. Using the PubMed database, an extensive literature search was performed on multinucleated giant cell (and epidermis, epithelial, and histiocytic) and herpes virus infection. Relevant papers were reviewed to discover the skin conditions with either multinucleated giant cells in the epidermis or coincident cutaneous herpes virus infection. Results: Initial skin biopsies from patients with either pemphigus vulgaris or transient acantholytic dermatosis mimicked herpes virus infection; however, laboratory studies and repeat biopsies established the correct diagnosis of their acantholytic dermatosis. Hence, epidermal multinucleated giant cells are not always a histopathologic clue to a herpes virus infection. Indeed, epithelial multinucleated giant cells in the epidermis can be observed not only in the presence of infection (herpes virus), but also acantholytic dermatoses and tumors (trichoepithelioma and pleomorphic basal cell carcinoma). Histiocytic multinucleated giant cells in the epidermis can be observed in patients with either giant cell lichenoid dermatitis or lichen nitidus of the palms. Conclusions: Epithelial and histiocytic multinucleated giant cell can occur in the epidermis. Keratinocyte-derived multinucleated giant cells are most commonly associated with herpes virus infection; yet, they can also be observed in patients with skin tumors or acantholytic dermatoses. Cutaneous herpes simplex virus infection can coexist in association with other conditions such as acantholytic dermatoses, benign skin tumors, bullous disorders, hematologic malignancies, inflammatory dermatoses, and physical therapies. However, when a herpes virus infection is suspected based upon the discovery of epithelial multinucleated giant cells in the epidermis, but either the clinic presentation or lack of response to viral therapy or absence of confirmatory laboratory studies does not support the diagnosis of a viral infection, the possibility of a primary acantholytic dermatosis should be considered and additional lesional skin biopsies performed. Also, because hematoxylin and eosin staining is not the golden standard for confirmation of autoimmune bullous dermatoses, skin biopsies for direct immunofluorescence should be performed when a primary bullous dermatosis is suspected since the histopathology observed on hematoxylin and eosin stained sections can be misleading.